ANOMIC AND DICHOTOMICAL ELEMENTS IN THE SEXIST DISCOURSE OF THE MEDIA (MEDIA REPRESANTATION OF WOMAN IN THE CLIP OF VIOLANCE AND DISCRIMINATION: THE SAMPLE OF AYŞEGÜL TERZİ) - Yağbasan, Mustafa; Barut, Merve (Karadeniz Teknik Üniversitesi, 2018)
As a social problem, behaviors and actions such as violence, brutality and torture have undoubtedly become an integral part of everyday life practice. While many parametres are the factors in this social problem, it is necessary to position the media as a separate entity. It is almost impossible to wake up to a new day without the news of a new murder of women in our country. Therefore, it is remarkable to understand that what is the position of the woman and how the violence applied to the woman in our country is reflected in the media. So, this attitude taken by the media is very important in terms of the formation and shaping of perceptions such as 'sex discrimination' and 'violence'. The case of Ayşegül Terzi is also the type that can serve as an example for the news in this category. The incident was reflected in the media on the first day of the feast in Istanbul / Maslak (on 16.09.2016) when a 23-year-old nurse Ayşegül Terzi was attacked by a man because of she was wearing shorts whom she did not know and this news was on the agenda for a long time. In this study,the representation of the woman in the written media and violence and discrimination applied to the woman was examined through this sample and the other violence cases were also tried to be examined. The research was limited to 3 newspapers (Sabah, Milliyet, Cumhuriyet) and (Bianet, Mynet, Yeni Akit) 3 internet sites with different publishing policies and ideologies with the date of Ayşegül Terzi incident and the following week between 16-22 September 2016. In this context, Ayşegül Terzi case is taken as a basis and included to other violence reports applied to the woman in th escope of the research. The study was conducted through the content analysis method of 30 articles compiled from newspaper and internet news articles between September 16th and 22nd, 2016. It has been determined that about 20 out of 30 articles about violence applied to the woman in the newspaper and internet news in the specified time are related to Ayşegül Terzi case and it is seen to be echoed with the way of informing. The most important finding of the study is that the case of Ayşegül Terzi (apart from the news value) is discriminated and seen as a news article. Because news in newspapers and websites with different publishing policies can not bring out a noticeable difference in turning violence into a legitimate issue, their news is not social, but ordinarized and transmitted to the individual case the violence that has been applied to the woman

Şiddet, vahşet veya işkence gibi davranış ve eylemler şüphesiz toplumsal bir sorun olarak gündelik yaşam pratiğinin adeta ayrılmaz bir parçası haline gelmiş durumdadır. Birçok parametrenin etken olduğu bu sosyal sorunda medya dahlinin ayrı konumlandırması gerekir. Zira her yeni güne yeni bir kadın cinayeti haberi ile uyanmanın neredeyse mümkün olmadığı ülkemizde kadına uygulanan şiddetin medyada yansıtılış şekli ve kadının konumlandırılış biçimi dikkat çekmektedir. Dolaysıyla medyanın takındığı bu tavır ‘cinsiyet ayrımcılığı’, ‘şiddet’ gibi algılarının oluşması ve şekillenmesi açısından da oldukça önem arz etmektedir. Ayşegül Terzi vakası da bu kategorideki haberlere örnek teşkil edebilecek türdendir. Söz konusu olay, İstanbul/Maslak’ta bayramın birinci günü, (16.09.2016 tarihinde) 23 yaşındaki Ayşegül Tezi isimli bir hemşirenin şort giymesi nedeniyle, tanımadığı bir erkek tarafından otobüste saldırıya uğraması ile medyaya yansımış ve uzun bir süre gündemde kalmıştı. Bu araştırmada şiddet ve ayrımcılık kıskacındaki kadının medyada temsili bahse konu olan bu örneklem üzerinden incelenmiş ve kadına uygulanan şiddet vakaları yazılı medya özelinde irdelenmeye çalışılmıştır. Araştırma, Ayşegül Terzi olayının olduğu gün ve müteakip haftayı kapsayan 16–22 Eylül 2016 tarihleri aralığı ile farklı yayın politikalarına ve ideolojilere sahip 3 gazete (Sabah, Milliyet, Cumhuriyet) ve 3 internet sitesi (Bianet, Mynet, Yeni Akit) ile sınırlandırılmıştır. Bu bağlamda Ayşegül Terzi vakası esas alınmakla birlikte, kadına uygulanan diğer şiddet haberleri de araştırma kapsamına dâhil edilmiştir. Çalışma, 16 – 22 Eylül 2016 tarihleri aralığında örnekleme dâhil edilen gazete ve internet sitesi haberlerinden derlenen 30 haberin içerik analiz yöntemi ile irdelenmesi marifetiyle yürütülmüştür. Belirlenen zaman aralığında, söz konusu gazete ve internet sitesi haberlerinde, kadına uygulanan şiddet haberlerinin 30’undan 20’sinin Ayşegül Terzi vakasına ilişkin haberler olduğu belirlenmiş ve haberin veriliş şekli ile yankı uyandırılmaya çalışıldığı görülmüştür. Çalışma sonucunda elde edilen en önemli bulgu ise, Ayşegül Terzi vakasının (haber değeri dışında) kadının ayrımcılığa uğraması ve bir haber metası olarak görülmesidir. Zira farklı yayın politikalarına sahip gazete ve internet sitesi haberleri bahse konu olan şiddeti habere dönüştürürken dikkat çeken bir farklılık ortaya koyamadıkları gibi haberleri toplumsal değil, bireysel vaka boyutuyla aktarmış ve kadına uygulanan şiddeti sıradanlaştırmışlardır
MEDYANIN CİNSİYETÇİ SÖYLEMİNDE ANOMİK VE DİKOTOMİK UNSURLAR: AYŞEGÜL TERZİ ÖRNEĞİ
Keywords: Communication and Media Studies; İletişim ve Medya Çalışmaları